Cellulose-g-poly(d-lactide) nanohybrids induced significant low melt viscosity and fast crystallization of fully bio-based nanocomposites. (2nd January 2017) - Ma, Piming; Shen, Tianfeng; Lin, Long; Dong, Weifu; Chen, Mingqing
Highlights: ⿢ NCC- g -PDLA nanohybrids were synthesized and used to make nanocomposites. ⿢ The melt viscosity of PLLA/PHA was significantly reduced by NCC- g -PDLA nanohybrids. ⿢ The crystallization of PLA was remarkably enhanced by NCC- g -PDLA nanohybrids. ⿢ Unique core-shell-like microstructures of the nanocomposites were formed. Abstract: Comb-like nanocrystal cellulose graft poly (d -lactide) (PDLA), i.e., NCC- g -PDLA nanohybrids were synthesized and compounded with poly (l -lactide) (PLLA) and poly (hydroxyalkanoate)s (PHA) to make fully biobased nanocomposites. Surprisingly, the complex viscosity of the PLLA/PHA melts was reduced by more than one order of magnitudes, viz. from 4000 to 100 Pa s by incorporation of 2⿿4 wt% of the NCC- g -PDLA nanohybrids. Meanwhile, the crystallization of the PLLA component was accelerated by the NCC- g -PDLA nanohybrids due to the strong interaction between PDLA and PLLA macromolecules. The significant reduction in melt viscosity associating with unique core-shell-like microstructures due to the synergetic effect of the NCC- g -PDLA nanohybrids and the PHA would facilitate the preparation of complex-shaped biomass articles and fibers under low(er) pressure and temperatures, which is beyond pure academic interest.